2014
DOI: 10.1111/hpb.12117
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open liver resection: a meta‐analysis of long‐term outcome

Abstract: Background: Laparoscopic liver resection is growing in popularity, but the long-term outcome of patients undergoing laparoscopic liver resection for malignancy has not been established. This paper is a meta-analysis and compares the long-term survival of patients undergoing laparoscopic (LHep) versus open (OHep) liver resection for the treatment of malignant liver tumours.Methods: A PubMed database search identified comparative human studies analysing LHep versus OHep for malignant tumours. Clinical and surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 33 publications
5
58
1
6
Order By: Relevance
“…First, comparative studies have shown that surgical margins were identical in open and laparoscopic surgeries [11]. In terms of long-term outcome, LLR and open liver surgery have comparable results for the overall and disease-free survival [55, 56, 64, 65]. Another advantage of LLR is that it may enhance the possibilities of subsequent liver transplantation for recurrent HCC or decompensation.…”
Section: Resultsmentioning
confidence: 99%
“…First, comparative studies have shown that surgical margins were identical in open and laparoscopic surgeries [11]. In terms of long-term outcome, LLR and open liver surgery have comparable results for the overall and disease-free survival [55, 56, 64, 65]. Another advantage of LLR is that it may enhance the possibilities of subsequent liver transplantation for recurrent HCC or decompensation.…”
Section: Resultsmentioning
confidence: 99%
“…This was confirmed in several retrospective comparative studies and meta-analyses that suggested additional advantages such as decreased pain, bleeding, morbidity and hospital stay using the laparoscopic approach as compared with open surgery [18,19]. Surgical margins and long-term survival were found not to be inferior [20]. The recognition of the efficacy and safety of LLR for HCC has led to the increased number of cases performed, especially among patients with peripheral tumors less than 5 cm [21,22].…”
Section: Western Perspectivesmentioning
confidence: 86%
“…Die verfügbaren Daten stammen aus multiplen Fallstudien [1,15], Fall-KontrollStudien [19], Übersichtsarbeiten [8] und Metaanalysen [21,23] …”
Section: Evidenz Der Laparoskopischen Leberchirurgieunclassified
“…Die durch die laparoskopische Operation bereits deutlich verkürzte Erholungszeit [8,17,21] kann durch adäquate Anäs-thesieverfahren mit Periduralkatheter, frühzeitige Mobilisation und Ernährung sowie die frühzeitige Entfernung aller invasiven Zugänge noch weiter abgesenkt werden [22,26] Weitere Entwicklungen der minimalinvasiven Leberchirurgie gehen mit der Entwicklung von Robotersystemen einher [30]. Hier ist die Bedeutung bisher nicht absehbar.…”
Section: Postoperativer Verlauf Und Fasttrackunclassified